Advances and development of prostate cancer, treatment, and strategies: A systemic review - Belkahla, Sana; Nahvi, Insha; Biswas, Supratim; Nahvi, Irum; Ben Amor, Nidhal (Frontiers in Cell and Developmental Biology, 2022)
Prostate cancer is considered as the most common malignant cancer in men in 12 regions of the world. For decades, it has been the second leading cause of cancer death among men worldwide. The prognosis of prostate cancer is mainly determined by the presence or absence of metastasis. Inspite of the considerable advancements achieved in the therapeutic management of cancer, it continues to be a challenge as most of these patients have no symptoms and it is a slow growing cancer although there are some cases of aggressive prostate cancer as well. In 2018, prostate cancer in Saudi Arabia represented 5% of all newly diagnosed cancers among Saudi males with an incidence around 5 to 6 cases per 100,000 men. Prostate cancer mortality rates have been low in comparison to incidence rates during the previous two decades due to a high rate of over diagnosis and overtreatment. The present review article is directed towards development, diagnostics via machine learning, and implementation of treatment of this cancer with special focus on nanotherapeutics, keeping in view the incidence of prostate cancer in the gulf countries.